DISCRETE AND INTEGRATED APPROACH AND THE IMPLICATIONS ON LANGUAGE TEACHING LEARNING MANAGEMENT - banun havifah cahyo khosiyono (Universitas Muria Kudus, 2021)
This paper describes discrete and integrated approach and the implication on language teaching learning management. Discrete approach emphasizes on the teaching and learning a language discretely, whereas integrated approach emphasizes on the whole language, namely speaking, writing, listening, reading, pronunciation, grammar, and vocabulary. In fact, both are interrelated since discrete learning is the basis for integrated learning. Both should be implemented in the teaching learning process in the classroom so that students are able to use the language well. Therefore, the curriculum or the syllabus, teaching materials, teachers’ qualification, and classroom management should be prepared well.